Minutes of the 4th Meeting of BRAC University Board of Trustees (BoT) - Board of Trustees (BoT), BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of the Minutes of 3rd Meeting of Board of Trustees. 2. Review of the progress of decisions of the 2nd Meeting of Board of Trustees. 3. Proposal for induction of new members in the Board of Trustees. 4. Review of the Minutes of the 5th Meetings of BRACU Syndicate. 5. Approval of the Proposal of Bachelor in Social Science (BBS) in Anthropology. 6. Approval of the Proposal for Centre for Urban Equity and Health (CUEH). 7. Approval of the Proposal for Centre on Gender and Social Transformation (CGST). 8. Approval of the Minutes of the Faculty Appointment Committee Meeting held on 22 November, 27 December 2011 and 11 & 12 January 2012. 9. Approval of the Appointments made by the staff Appointment Committee held on 12 & 14 December 2011. 10. Report on Preparation for the 7th Convocation. 11. Report on progress on Permanent Campus. 12. Miscellaneous: 12.1 Admission Test. 12.2 Appeal seeking withdrawal of expulsion and continuation of study in BRAC University.